How does maternal occupation (specifically exposure to work stress and long working hours) affect the risk of low birth weight infants? : A Systematic Review - Rizky Febriansyah; Bangar Parlinggoman Tua; Mutia Juliana; Aditya Rifandi Zaenudin (International Medical Journal Corp. Ltd, 2026)
Introduction: Maternal employment during pregnancy is increasingly common, yet the impact of work-related stress and long working hours on low birth weight (LBW) remains inconclusive. This systematic review synthesizes evidence from observational studies examining associations between maternal occupational exposures—specifically psychosocial work stress, job strain, and long working hours—and the risk of LBW infants. Methods: A systematic review of 17 sources published to 2025 was conducted. Studies were included if they examined employed pregnant women, assessed work-related stress or working hours, reported LBW (<2500g) as an outcome, and provided quantitative data. Data extraction covered work exposures, population characteristics, LBW outcomes, related pregnancy outcomes, study design, confounders, and dose-response evidence. Results: Long working hours (>40 h/week) were associated with significantly increased odds of LBW in the largest meta-analysis (OR 1.43, 95% CI 1.11–1.84), though other reviews found no significant association. Psychosocial work stress showed non-significant association with dichotomous LBW (OR 2.30, 95% CI 0.70–7.60) but significantly reduced mean birthweight by 77 grams (95% CI −121.18 to −33.01). Physically demanding work demonstrated consistent association with small-for-gestational-age infants (OR 1.37, 95% CI 1.30–1.44). Preterm delivery showed modest associations with long hours (OR 1.16–1.21) and shift work (OR 1.13–1.21). Dose-response evidence was limited, though declining effort-reward imbalance across pregnancy was associated with 408 g higher birthweight. Discussion: The evidence is heterogeneous, with effect estimates moderated by exposure specificity, study quality, and outcome measurement. Psychosocial stress affects continuous birthweight more consistently than dichotomous LBW, suggesting mechanistic pathways through neuroendocrine disruption of placental perfusion. Long working hours operate primarily through preterm delivery rather than fetal growth restriction. Higher-quality studies yield smaller estimates, and confounding control remains inadequate. Conclusion: Maternal work stress and long hours are associated with modest but significant reductions in birthweight and increased preterm delivery risk. However, certainty is low due to observational designs and heterogeneity. Future research requires prospective designs with repeated exposure measures, adequate confounding control, and standardized outcomes.